Activity-Based Costing as a Strategy to Improve Production Efficiency - Wahyu Setyawan (PT. Hafasy Dwi Nawasena, 2025)
In the era of globalization and digital transformation, companies face competitive pressures that demand cost efficiency and information accuracy in decision making. Traditional costing systems often fail to reflect the complexity of modern production activities, thus risking distortion of cost information. Activity-Based Costing (ABC) is present as an alternative approach that is more accurate and strategic, by allocating costs based on activities that trigger resource consumption. This study uses a qualitative method with a case study of a manufacturing company that has implemented ABC, to explore the contribution of this system to increasing operational efficiency. Data were collected through interviews, observations, and documentation studies, and analyzed thematically to identify patterns of relationships between activities, costs, and managerial strategies. The results of the study show that ABC not only improves the accuracy of cost information, but also functions as a strategic tool in decision making, product planning, process efficiency, and customer value creation. By revealing value-added and non-value-added activities, ABC enables companies to design cost-saving strategies without sacrificing quality. Therefore, ABC is not just a cost system, but a strategic framework that is adaptive to market dynamics and supports sustainable competitive advantage.